(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article discovers the aesthetic base in the formation of harmonious pupil’s personality in modern Ukrainian school. The author proves that realization of sociocultural direction of Ukrainian language is impossible without due regard for some conditions, particulary conducting of aesthetic notions, creating conditions when interiorization of aesthetic demand into self-demand is realized.